2020
DOI: 10.1099/mic.0.000884
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to pH stress by Vibrio fischeri can affect its symbiosis with the Hawaiian bobtail squid (Euprymna scolopes)

Abstract: Many microorganisms engaged in host-microbe interactions pendulate between a free-living phase and a host-affiliated stage. How adaptation to stress during the free-living phase affects host-microbe associations is unclear and understudied. To explore this topic, the symbiosis between Hawaiian bobtail squid (Euprymna scolopes) and the luminous bacterium Vibrio fischeri was leveraged for a microbial experimental evolution study. V. fischeri experienced adaptation to extreme pH while apart from the squid host. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 71 publications
(145 reference statements)
0
13
0
Order By: Relevance
“…Vibrionaceae are found world-wide, in brackish environments with disparate and fluctuating pH conditions reflecting changing organic nutrient load, dissolved organic carbon levels, and active geologic activity [ 40 , 41 ]. While even small pH changes can dramatically impact microbial communities such as the Vibrionaceae, V. fischeri has evolved to thrive in the microenvironment of the light organ, where the matrix pH changes dramatically during the diel cycle, gradually decreasing from a pH ~7.0 after venting at dawn, to a pH ~5.5 just prior to the next venting event [ 42 , 43 ]. This is in agreement with experimental work exhibiting several V. fischeri strains able to grow in culture between pH 5–10.6 [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vibrionaceae are found world-wide, in brackish environments with disparate and fluctuating pH conditions reflecting changing organic nutrient load, dissolved organic carbon levels, and active geologic activity [ 40 , 41 ]. While even small pH changes can dramatically impact microbial communities such as the Vibrionaceae, V. fischeri has evolved to thrive in the microenvironment of the light organ, where the matrix pH changes dramatically during the diel cycle, gradually decreasing from a pH ~7.0 after venting at dawn, to a pH ~5.5 just prior to the next venting event [ 42 , 43 ]. This is in agreement with experimental work exhibiting several V. fischeri strains able to grow in culture between pH 5–10.6 [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study investigating the impact that global climate change driven acidification of ocean waters (increasing atmospheric CO 2 leading to increased levels of dissolved CO 2 that forms carbonic acid) will have upon the E. scolopes–V. fischeri symbiosis, it was found that the V. fischeri that was experimentally evolved under low pH (6.0 vs. 7.4) growth conditions for multiple generations outcompeted non-evolved ancestor V. fischeri strains in colonizing juvenile squid [ 43 ]. Additional studies used a similar experimental evolution approach to assess how adaptation to a low pH environment affects V. fischeri growth rates and bioluminescence production, and squid colonization demonstrated significant increases in colonization rates, faster generation times, and increased bioluminescence compared to ancestral wild-type strains [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The light organ of bobtail squid is one of the best characterized, comprising both internal crypts that house symbionts and external structures that are lost after symbiont colonization [23,29]. The crypts are acidic and enriched with host antimicrobials, selecting for light-producing Vibrio fischeri, creating an environment that is inhospitable to most other microbes, and increasing the availability of oxygen for light production [23,29,30].…”
Section: Bioluminescencementioning
confidence: 99%
“…Moreover, how these stressors can drive increased bacterial diversity in the free-living state and hosts is addressed. Three interesting empirical case studies have been completed with temperature and pH quite recently, which readers are encouraged to read (Cohen et al, 2019(Cohen et al, , 2020Nourabadi and Nishiguchi, 2021).…”
Section: Introductionmentioning
confidence: 99%